Study of Some Immunity Characters Results of Injection antigenic Staphyloccocus sp. in Local Rabbits - Roua Jamal AbdulKhaliq1 , Hiba M. AlKhateeb2 , Abdalwahab Bdewi Hussain3, A. O. Humide3 (Institute of Medico-legal Publications Pvt Ltd, 2021)
This study was conducted to identify some immune manifestations resulting from the injection ofstaphylococcal bacterium antigens Heat-killing with a concentration of 0.75 ml in muscle and concentration0.5 ml subcutaneous in local rabbits to see how immune response of these antigens achieve. Tests werecarried out (late hypersensitivity, phagocytosis of candida albicans, and NBT dye reduction).The results showed that the highest level of skin thickness was 9.50 ml compared to control 1.48 ml after 24hours of antigen injection. The results also showed that the highest level of candida yeast is 81.30% wheninjecting concentration 0.5 ml under the skin compared to control 79.33%. As for the reduction of NBT dye,the highest level of dye reduction was 14.70% when the concentration was injected 0.75 ml with the musclecompared to 10.63% control.We conclude that the injection of staphylococcus antigens (killed by heat) has the potential to induce immuneresponse in local rabbits